Kajian Kebutuhan Peningkatan Kompetensi Mengajar Guru - Mahdiansyah -- (Jurnal Pendidikan dan Kebudayaan, 2010)
This study aims to identify the objective read of the school needs objectively which can be taken into account in determining policy intervention through educational planning. The specific aims of the study are to obtain information on: a) teacher characteristics perceived as determinants of teacher quality b) teacher quality which focuses on their competence in teaching and learning process and need assessment of teacher training. Findings of the study show that there are many teachers whose educational backgrounds did not match with the subject they teach (mismatch). This is especially true in the case of private junior and senior secondary school teachers. There was a concern on the mastery of primary school teachers in the subjects they teach. At the junior and senior secondary levels most of the teachers had the mastery in most parts of the subjects they teach. Attempts to improve teacher professionalism were conducted through training. However, more than two fifth of teachers did not participate in any training. Training on how to develop curriculum and tests were needed by most of Islamic primary, junior secondary and senior secondary teachers who had non-teaching qualification background.Â ABSTRAKTujuan studi ini adalah untuk mengidentifikasi kondisi obyektif kebutuhan sekolah, yang dapat dijadikan dasar dalam menentukan intervensi kebijakan melalui perencanaan program pendidikan. Secara khusus studi ini dimaksudkan untuk mengetahui: (a) karakteristik guru yang dipandang sebagai determinan kualitas guru, dan (b) kualitas guru yang difokuskan pada kompetensi guru dalam proses belajar mengajar dan identifikasi kebutuhan pelatihannya. Hasil studi menunjukkan bahwa latar belakang guru banyak yang tidak sesuai dengan mata pelajaran yang diajarkan (mismatch), terutama guru SMP/MTs dan SMA/SMK/MA yang berasal dari sekolah swasta. Penguasaan guru SD/MI terhadap materi pelajaran yang menjadi tanggung jawabnya masih memprihatinkan. Namun, guru SMP/MTs dan SMA/SMK/MA sudah menguasai sebagian besar materi mata pelajaran. Upaya untuk meningkatkan profesionalisme guru dilakukan melalui kegiatan pelatihan, meskipun lebih dari dua perlima guru tidak pernah mengikuti penataran/pelatihan. Pelatihan tentang pengembagan kurikulum dan penyusunan tes dibutuhkan hampir oleh semua guru, terutama guru MI, MTs dan MA serta guru yang berlatar belakang pendidikan nonkeguruan.